2018
DOI: 10.4995/riai.2017.8819
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación Neurofisiológica del Entrenamiento de la Imaginación Motora con Realidad Virtual en Pacientes Pediátricos con Parálisis Cerebral

Abstract: Existen diversas evidencias que indican que los déficits motores en los pacientes de parálisis cerebral se asocian con problemas en la planificación motora que, a su vez, apuntan a una mermada capacidad para imaginar movimientos. La imaginación motora se ha revelado como una herramienta efectiva en el aprendizaje y la adquisición de habilidades motoras ya que comparte estructuras neuronales similares con la ejecución motora. En este trabajo se presenta un paradigma basado en un juego de realidad virtual para g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
0
5
0
7
Order By: Relevance
“…Nonetheless, to the best of our knowledge, there is only a limited number of this type of studies involving children with CP. Furthermore, given the aforementioned difficulties concerning their MI capability, it becomes essential to initially tackle the problem by exploring whether such patients can exhibit the expected response for MI in the form of contralateral event-related desynchronizations (ERDs), usually established as the "gold standard" for the MI response that can be detected with EEG [25][26][27], and frequently the measure of interest in EEG-NFBT MI-based applications (e.g., [23,28,29]).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, to the best of our knowledge, there is only a limited number of this type of studies involving children with CP. Furthermore, given the aforementioned difficulties concerning their MI capability, it becomes essential to initially tackle the problem by exploring whether such patients can exhibit the expected response for MI in the form of contralateral event-related desynchronizations (ERDs), usually established as the "gold standard" for the MI response that can be detected with EEG [25][26][27], and frequently the measure of interest in EEG-NFBT MI-based applications (e.g., [23,28,29]).…”
Section: Introductionmentioning
confidence: 99%
“…In that study, eight subjects were randomly separated into two groups: sham and active tDCS. Results showed that for the active tDCS group, the central electrodes Cz, C3 and C4 had the highest volume of epochs with significant values of partial directed coherence (PDC) for alpha (8)(9)(10)(11)(12) and beta (13-30 Hz) frequency bands. The current research expands that work to four new subjects, detailing the nature of the inflow and outflow interactions that show a different behavior for the rest and imagine periods in a repetitive way for all the subjects in a group.…”
Section: Study Of Functional Brain Connectivity and Lower-limb Motor Imagery Performance After Tdcsmentioning
confidence: 99%
“…Their applications can allow a person to interact with a computer by only using their brain activity, [3][4][5] or help impaired people during physical rehabilitation and assistance. [6][7][8] The first evidence of EEG patterns related to movement was detected in 1965, 9 showing a slow negative EEG activity preceeding self-initiated movement by low potentials. 10,11 In 1994, 12 the relationship with event synchronization over motor areas was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, existen varios grupos de personas a los que estos avances tecnológicos no han sido capaz de alcanzar. Uno de estos grupos es gente con discapacidades motoras (Del-Castillo et al, 2018).…”
Section: Introductionunclassified